Sistem maklumat pengurusan berdasarkan kajian keberkesanan sistem maklumat kajian kes : Unit Penguatkuasa, Majlis Perbandaran Kulai (MPKu) - Mat Surin, Ely Salwana (2006)
The evolutions of using information system in almost organizations produce more systematic management activities. Therefore, this project is developed to fulfill the organization requirement, which is to Develop Management Information System Based on Research on Effectiveness of Information System Services. Developer use Unit Penguatkuasa, Majlis Perbandaran Kulai (MPKu) as a case study. The objective of the system is to support Information System effectiveness model that will be used and at the same time to make sure management process at MPKu will be more easy and smooth. The model that will be used is Reformulated Model from McLean and DeLone. The system is very important to make sure Unit Penguatkuasa will be delivered better services and besides, it also can increase a quality of management at this Unit. The system development will use a prototype evolution and object oriented modeling. The development processes only focus on Unit Penguatkuasa, Majlis Perbandaran Kulai (MPKu). Micomedia Dreamweaver MX will be use for editing process, while Active Server Pages (ASP) will be used as a programming language. For the database, developer will use Microsoft SQL Server 7. As a conclusion, hopefully this project will fulfill the user requirements, which is to produce effective information system application.